(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the impact of modern technologies on philosophical and ethical theory. It discusses how technological development affects human life, society, and ethical values. Technologies, including artificial intelligence, biotechnology, and the digital revolution, raise philosophical issues such as ethical decisions, human freedom, privacy, and information security. Philosophy plays a significant role not only in understanding these technologies but also in evaluating their social consequences. The importance of philosophical approaches in critical thinking, ethical responsibility, and making conscious decisions is discussed, as well as the future social and ethical impacts of technologies. The article presents key ideas and recommendations necessary for properly understanding the relationship between humans and technology in a technological society.